2007
DOI: 10.1074/jbc.m702122200
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell FRET Microscopy

Abstract: The adrenoleukodystrophy protein (ALDP) and the 70-kDa peroxisomal membrane protein (PMP70) are half-ATP-binding cassette (ABC) transporters in the mammalian peroxisome membrane. Mutations in the gene encoding ALDP result in a devastating neurodegenerative disorder, X-linked adrenoleukodystrophy (X-ALD) that is associated with elevated levels of very long chain fatty acids because of impaired peroxisomal ␤-oxidation. The interactions of peroxisomal ABC transporters, their role in the peroxisomal membrane, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…The ABC transporter within the complex is composed mainly of ALDP or PMP70 homo-oligomers, which is consistent with reports from earlier studies (16). However, we again confirmed that ALDP also has the capacity to bind PMP70 in vivo.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The ABC transporter within the complex is composed mainly of ALDP or PMP70 homo-oligomers, which is consistent with reports from earlier studies (16). However, we again confirmed that ALDP also has the capacity to bind PMP70 in vivo.…”
Section: Discussionsupporting
confidence: 83%
“…2A) showed that ALDP had a significant higher affinity (p Ͻ 0.01) to form homo-oligomers (BRET 50 , 0.85) than heterooligomers with PMP70 (BRET 50 , 2.05). These findings are in line with those obtained by FRET (16). In addition, the data may suggest that PMP70 has a comparable affinity to homo-oligomerize (BRET 50 , 1.22) and is more likely to exist as a homooligomeric than a hetero-oligomeric transporter (this difference was not statistically significant).…”
Section: Characterization Of Protein Complex Architectures By Bretsupporting
confidence: 81%
See 2 more Smart Citations
“…Although a mirror expression pattern is often observed between ALDP and ALDRP when specific cell types are analyzed (9), peroxisomal ABC transporters have overlapping expression patterns rendering possible such interactions (5, 10). Coimmunoprecipitation experiments or FRET analysis have demonstrated heterodimerization in cells overexpressing the peroxisomal ABC transporters (11,12). Although the peroxisomal localization of ALDP, ALDRP, and PMP70 is clearly demonstrated, PMP69 has recently been described to be localized in the endoplasmic reticulum and was found to be absent in the peroxisome.…”
mentioning
confidence: 99%